Spiritual wellbeing in breast and cervical cancer survivors: differences in each stage of survivorship - Ni Putu Wulan Purnama Sari (Intelektual Pustaka Media Utama, 2019)
Spiritual needs in cancer survivors are underappreciated compared to physical and psychological needs. This study aimed to: 1) compare and analyze the differences in spiritual wellbeing (SWB) between breast and cervical cancer survivors (BCS and CCS) generally, and between stages of survivorship specifically, and 2) determine the best predictor of SWB in both cases. This cross-sectional study involved 58 BCS and 47 CCS (n=105). Questionnaire of QOL-CS part IV was used in data collection. Various statistical tests were used in data analysis (α<0.05). SWB was significantly different between BCS and CCS (p=0.002), which influenced by significant differences in religious activity, spiritual activity, uncertainty, positive life changes, life goals, and hope (all p<α). In BCS, overall SWB was not significantly different between survivorship stages (p=0.179); but religious activity, life goals, and hope were significantly different (p=0.043, p=0.022, and p=0.036 respectively) which indicate that these three aspects change overtime along with the survivorship stages. While in CCS, SWB and all of its aspects were not significantly different between survivorship stages (all p>α) which indicate that SWB is stable/stagnant across the survival life span in CCS. Spiritual life changes and religious activity are the best predictors of SWB in both cases and were accounted for 70.3% (R2=0.703) and 69.7% (R2=0.697) variance of SWB in BCS and CCS respectively.